Dissecting the Ethics Court in Indonesia: Problems and Future Regulations from a Legal Philosophy Perspective - Nheo Adi Kurniawan; Deva Mahendra Caesar Bimantya; Zerry Akbar Yudisetyo (NOVUM : JURNAL HUKUM, 2025)
The term "ethics court" has become one of the most interesting terms in Indonesia, given the existence of various institutions that enforce ethical codes within the public official sphere and various specific professions. Despite this, there are issues regarding the status of ethical courts in Indonesia, with debate over whether such courts exist or not. This research aims to analyze and reflect on the development of ethics courts in Indonesia, including their problems and future regulations, from a legal philosophy perspective. This research is normative legal research with philosophical, conceptual, case, and legislative approaches. The research findings confirm that from the perspective of positive law in Indonesia, ethics courts still function as administrative instruments subject to the formal legal system, and are therefore not yet able to play an autonomous role in substantively upholding the integrity and morality of the profession. The lack of a clear distinction between the domains of ethics and law obscures the function of ethical courts as protectors of professional dignity and public morality. From a legal philosophy perspective, forward-looking regulations are needed to balance the principles of morality and legal certainty with the strengthening of a solid legal foundation, recognition of independence, and the final authority of ethics courts. Thus, the forward-looking regulatory strategy aims to make the ethics court a pillar of substantive justice that respects universal moral values while also providing legal certainty in the conduct of an integrated state.